Epidemiological profile and prevalence of clinical and serological disability among candidates for blood donation / Perfil epidemiológico e prevalência de inaptidão clínica e sorológica entre candidatos à doação de sangue - Eleuterio, Tatiana de Araujo (2023)
Objective: to describe the epidemiological profile and identify the prevalent causes of clinical and serological unfitness among donation candidates in the last five years. Methods: this is a cross-sectional, exploratory and analytical study. Data were obtained using the Hemote Plus® System. Results: most candidates were men (50.9%), aged 20 to 29 years (34.0%), white (66.7%), single (59.9%) with high school education (33.3 %) and spontaneous motivation (65.5%). Among them, 25.9% were considered unfit. The most prevalent causes of disability were: anemia (27.7%) and sexually transmitted infections (12.4%). Women (57.9%), individuals with a lower level of education (53.9%), and those with less than 39 years of age (65.5%) tended more toward sdisability. Conclusion: it is evident the need for educational practices and guidance on risk behaviors in the recruitment of donors and clinical screening, emphasizing the importance of the nursing professional in this context.